PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS V PADA PELAJARAN IPAS MATERI DAERAHKU KEBANGGAANKU DI SDN 101879 - Putri, Fedrina Ananda; Sitohang, Risma (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to determine the effect of implementing the Make A Match Type Cooperative learning model on student learning outcomes at SDN 101879 Kanan II in Class V Semester II 2023/2024 Academic Year. The type of research used is Quasi Experiment with a Pretest Posttest Control Group Design research design. The sample in this study used 2 classes with a total of 30 students. Research instrument techniques include Validity Test, Reliability Test, Difficulty Level Test and Distinguishing Power Level Test. Data analysis techniques through Normality Test and Hypothesis Test. Based on the pretest results, the experimental class was 54.37 and the control class was 56.07. The average posttest score for the experimental class was 85.62 and the control class was 66.25. The total increase in pretest and posttest scores in the experimental class was 31.25 while the control was 10.18. Data analysis uses the normality test with the Kolmogorov-Smirnov formula, hypothesis testing uses the t-test. In the pretest normality test in the experimental class, namely KShitung < KStabel of 2.14 < 2.27, while in the control class, namely KShitung < KStabel of 1.72 < 2.13, both classes had a normal distribution. The posttest normality test in the experimental class was KShitung < KStabel and the control class was KShitung < KStabel of 1.62 < 2.1, both classes had a normal distribution. In the hypothesis test, the posttest value obtained in the experimental class was ð‘¡â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” â‰¥ ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™, namely 11.70 â‰¥ 1.75 and the control class was ð‘¡â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” â‰¥ ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™, namely 7.65 â‰¥ 1.77, with a significance level of Î±=0.05. From this research it can be concluded that there is an influence of the make a match learning model on the learning outcomes of class V students in science and science lessons, my pride, my region at SDN 101879 Kan II T.A 2023/2024.Keywords: Learning model, make a match, learning outcomes